2022
DOI: 10.1111/jop.13333
|View full text |Cite
|
Sign up to set email alerts
|

SPP1 as a key gene in the lymph node metastasis and a potential predictor of poor prognosis in head and neck carcinoma

Abstract: Background: Lymph node metastasis (LNM) is an important cause leading to recurrence and development of head and neck carcinoma (HNC), with the precise mechanisms unclear. Thus, we aimed to identify the key genes involved in LNM and further evaluate their expressions and roles.Methods: A cohort of HNC in the TCGA was analyzed. The study involved three phases (one screening and two validation phases). First, the differentially expressed genes regarding LNM were screened, from which a key gene was identified by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…The RNA interference technique was utilized. Stable SERPINE1 -knockdown cell lines were established according to the methods described recently [ 14 ]. Two cancer cell lines, CAL27 and SAS, were chosen for further exploration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA interference technique was utilized. Stable SERPINE1 -knockdown cell lines were established according to the methods described recently [ 14 ]. Two cancer cell lines, CAL27 and SAS, were chosen for further exploration.…”
Section: Methodsmentioning
confidence: 99%
“…A tissue microarray of oral cancer patients (HOraC060PG01) was purchased from Shanghai Outdo Biotech Company. The characteristic of the patients was described A c c e p t e d A r t i c l e previously [14]. SERPINE1 protein expression was measured by immunohistochemistry (IHC) assay.…”
Section: Tissue Sample Analysismentioning
confidence: 99%
“…And in pancreatic adenocarcinoma, SPP1 expression levels were associated with patient prognosis and immune regulation (Chen et al, 2022), and in lung adenocarcinoma, SPP1 was found to be associated with drug resistance (Matsubara et al, 2022). In a recent study, researchers further investigated the level of serum SPP1 autoantibodies in patients with esophageal squamous cell carcinoma (ESCC) and showed that its expression was signi cantly upregulated compared to the normal group, suggesting that anti-SPP1 autoantibodies are a novel biomarker for the detection of ESCC , and SPP1 is important in prostate cancer (PCa), head and neck cancer (HNC), cervical squamous cell carcinoma (SCC) and other cancers (Zhang et al, 2022, Feng et al, 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Stable MYO1B-knockdown cell lines were established according to the methods described in our previous study. 38 DOK-trans and SAS were selected for further study. The cells with stable MYO1B-silence were named sh-MYO1B-DOK/trans and sh-MYO1B-SAS, while the relevant controls were named sh-NC-DOK/ trans and sh-NC-SAS, respectively.…”
Section: Establishment Of Stable Myo1b-knockdown Cell Linesmentioning
confidence: 99%